2010
DOI: 10.1021/om900843h
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Theoretical Study on Homopolymerization of α-Olefins by Bis(cyclopentadienyl) Zirconocene and Hafnocene: Elemental Propagation and Termination Reactions between Monomers and Metals

Abstract: A comparative quantum chemical study has been performed to shed light on the fundamental differences between hafnocenes and zirconocenes concerning reactions between the metals and R-olefin monomers, namely, ethene, propene, 1-butene, and 1-hexene. Analogous species along the R-olefin polymerization pathways were studied for bis(cyclopentadienyl) zirconocene and hafnocene, taking into account the structural variations of the first two monomer insertion steps and of the competitive chain-termination reactions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…The difference between the zirconocene 10 a and the hafnocene 10 b is the amount of regioerrors (Table 2, entries 1–3 and 5–7). For [Cp 2 MCl 2 ] (M=Zr, Hf) theoretical investigations show the same trend as the energy difference between the transition states of a 1,2 and a 2,1‐insertion is higher for the hafnocene compared to the corresponding zirconocene species 23…”
Section: Effect Of 24‐substitution On the Indenyl Moiety Of Differenmentioning
confidence: 66%
See 1 more Smart Citation
“…The difference between the zirconocene 10 a and the hafnocene 10 b is the amount of regioerrors (Table 2, entries 1–3 and 5–7). For [Cp 2 MCl 2 ] (M=Zr, Hf) theoretical investigations show the same trend as the energy difference between the transition states of a 1,2 and a 2,1‐insertion is higher for the hafnocene compared to the corresponding zirconocene species 23…”
Section: Effect Of 24‐substitution On the Indenyl Moiety Of Differenmentioning
confidence: 66%
“…For [Cp 2 MCl 2 ] (M= Zr, Hf) theoretical investigations show the same trend as the energy difference between the transition states of a 1,2 and a 2,1-insertion is higher for the hafnocene compared to the corresponding zirconocene species. [23] Additionally, there is a clear dependency of propene concentration on the amount of stereodefects (entries 7 and 8). The formation of a stereoerror is known to proceed either through the choice of the "wrong" enantioface of the monomer or due to a chain end epimerization process (CEP).…”
mentioning
confidence: 99%
“…Although many computational studies have been carried out on these complexes and their role in oligo-and polymerization reactions (67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83), the electronic structures and relative energies of relevant reactants, intermediates, and transition states are computed with the same method used for optimizing the geometries for NMR calculations for consistency. ZrEt + is more deshielded in both the β-H and α-H agostic structures, but this effect is much more pronounced in the latter (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, Pakkanen et al demonstrated different possibilities of 1,2 and 2,1 propylene attack to Cp 2 MCH 3 + (M = Zr, Hf ) based on the regiostructures as well as stereostructures. 59 As a result, four products are formed in each combination of the two successive insertion steps which are 1,2 and 1,2, 1,2 and 2,1, 2,1 and 1,2, and 2,1 and 2,1 insertions (Scheme 2). There are other different possibilities in propylene attack, the propylene CH 3 group being up or down.…”
Section: Resultsmentioning
confidence: 99%